The Effect of Mental Health and Work-Life Balance on Job Satisfaction, with Psychological Capital as A Mediating Variable, at BPJS Kesehatan Branch Offices in Jakarta - Tri Islamiati; Corry Yohana; Widya Parimita (PT. Publikasiku Academic Solution, 2026)
Employee job satisfaction plays a crucial role in enhancing organizational performance, particularly within public service institutions that operate under demanding workloads, continuous organizational changes, and complex service responsibilities. Employees of BPJS Kesehatan are expected to sustain high performance while coping with various work-related challenges that may influence their psychological well-being. This study investigates the effects of mental health and work-life balance on job satisfaction, with psychological capital serving as a mediating variable among employees of BPJS Kesehatan Branch Offices in Jakarta. A quantitative research approach with a cross-sectional design was adopted. The study involved 231 respondents selected through proportionate stratified random sampling from the employee population. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that both mental health and work-life balance exert positive and significant effects on employee job satisfaction. In addition, these two variables significantly enhance psychological capital, which in turn positively influences job satisfaction. The mediation analysis further demonstrates that psychological capital significantly mediates the relationships between mental health, work-life balance, and job satisfaction. These results emphasize the importance of fostering optimism, hope, self-efficacy, and resilience as key psychological resources to improve employee satisfaction. The findings also offer practical insights for BPJS Kesehatan in designing human resource strategies that promote employee well-being and support sustainable organizational performance.